2021
DOI: 10.3390/sports9110155
|View full text |Cite
|
Sign up to set email alerts
|

Slow and Steady, or Hard and Fast? A Systematic Review and Meta-Analysis of Studies Comparing Body Composition Changes between Interval Training and Moderate Intensity Continuous Training

Abstract: Purpose: To conduct a systematic review and multilevel meta-analysis of the current literature as to the effects of interval training (IT) vs moderate intensity continuous training (MICT) on measures of body composition, both on a whole-body and regional level. Methods: We searched English-language papers on PubMed/MEDLINE, Scopus, CINAHL, and sportrxiv for the following inclusion criteria: (a) randomized controlled trials that directly compared IT vs MICT body composition using a validated measure in healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 105 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…I 2 values of 25%, 50%, and 75% correspond to small, moderate, and large amounts of heterogeneity respectively [34]. Q statistic value of 75-100 is considered as substantial heterogeneity [35]. LFK index and the symmetry of the Doi plot were used to assess publication bias.…”
Section: Methodsmentioning
confidence: 99%
“…I 2 values of 25%, 50%, and 75% correspond to small, moderate, and large amounts of heterogeneity respectively [34]. Q statistic value of 75-100 is considered as substantial heterogeneity [35]. LFK index and the symmetry of the Doi plot were used to assess publication bias.…”
Section: Methodsmentioning
confidence: 99%
“…We observed small changes in fat mass, and those, were not statistically significant. According to a recently meta-analysis, authors suggest that interval training is only effective to reduce small amounts of fat independently of the training protocol, intensity and duration, also, these findings suggest that focusing on greater volumes of exercise, instead of intensity, could be explored in order to see significant changes in fat mass (Steele et al, 2021). Further research concluded that body fat may not show differences in fat reductions in interval training programs that include lower time execution and lower energy expenditure when compared to a moderate intensity continuous training; it may important to consider that an acceptable volume of energy expenditure is required for fat reduction (Keating et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…some studies reporting reduced FM in healthy males and females following 4 weeks of HIIT program [12] and in individuals with overweight or obesity following 6 weeks of HIIT program [41]. On the other hand, research reported that FM was unchanged in response to short-term [12,42] and long-term HIIT interventions [43] in healthy individuals, which was supported by recent meta-analyses reporting that short-term HIIT/SIT is very unlikely to produce biologically important reduction in FM [44,45]. In support of this finding, Costigan et al [30] documented that HIIT performed ≥8 weeks is more effective in improving body composition compared to those with <8 weeks in duration.…”
Section: Accepted Manuscriptmentioning
confidence: 91%